Pengaruh Eksperimen Sains Hujan Warna Dari Bahan Alam Terhadap Kognitif Anak Usia 5-6 Tahun Di Taman Kanak-Kanak Dharma Wanita Kabupaten Lima Puluh Kota - Gatun Najah, Tari; Mahyuddin, Nenny (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2023)
This research is motivated by the fact that children's cognitive recognition of colors has not yet developed optimally. This media helps children recognize colors beyond what they see visually. The purpose of this study was to examine how effective the color rain experimental media was in introducing colors to children at the Dharma Wanita Kindergarten in 50 Kota District. The research form was Quasy Experiment using a quantitative approach. The population is Dharma Wanita Kindergarten children in 50 Kota districts. The sampling method is cluster sampling, namely 2 classes with a total of 30 children. Data collection is a test in the form of five questions and data analysis techniques include normality tests, homogeneity and finally hypothesis testing using SPSS 22 software. The conclusion of the research is that color rain science media has a significant effect compared to using magazine media with a value of 0.047 > 0.05 (2-tailet). Achievement effect size of 1.46 which is included in the high category. So the use of color rain science experiment media for children's color recognition is very effective.